English Teachers' Perceived Benefits and Challenges of Flipped Classroom Implementation - Muhammad Ansori; Nahar Nurun Nafi’ (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2018)
Although the flipped classroom has attracted much attention, the flipped classroom research in the English teaching context has not been widely explored. This research is intended (1) to explore the general responses of English teachers toward the flipped classroom methodology and (2) to investigate the perceived benefits and challenges of its implementation in English teaching. The total of 10 English teachers from different institutions that applied flipped classroom participated in this research. The data were collected byusing questionnaire and interviews. The data were analyzed by using quantitative descriptive and qualitative data analysis. The results reveal that English teachers have positive responses to the flipped classroom methodology. Some perceived benefits of its implementation are facilitating active learning, developing collaborative teamwork, stimulating autonomous learning, and increasing classroom interaction. Meanwhile, the perceived challenges of its implementation deal with supporting facilities, technical and technological problems, and the challenge of creating flipped learning material.